Numerical study of a MIL101 metal organic framework based desiccant cooling system for air conditioning applications. (September 2017) - Bareschino, Piero; Diglio, Giuseppe; Pepe, Francesco; Angrisani, Giovanni; Roselli, Carlo; Sasso, Maurizio
Graphical abstract: Highlights: A novel MIL101 based Desiccant Wheel (DW) was numerically investigated. 1D Heat and Mass balances were used to assess performances of desiccant wheel. MIL101 based DW has higher dehumidification effectiveness than silica gel based DW. Insertion of the MIL101 based DW in an air handling unit was simulated using TRNSYS™. Very interesting energetic, environmental and economic performances were forecast. Abstract: The use of a MIL101@GO-6 (MILGO) based Desiccant Wheel in a desiccant cooling system for air conditioning has been numerically studied. MILGO is a novel composite material, consisting of 6% w/w graphite oxide dispersed in the MIL101 metal organic framework network structure (J. Yan et al., Appl. Therm. Eng. 84, 118, 2015), and benefits from an outstanding water uptake, about 6 times greater than that of conventional silica gel adsorbent. A previously validated gas side resistance mathematical model has been used to evaluate the performances of the MILGO based desiccant wheel, finding that its dehumidification effectiveness is about 30% higher than that of a conventional silica gel based desiccant wheel under the simulation conditions tested. Additionally, using a simplified effectiveness method, the performances of an air handling units equipped with this novel desiccant wheel, interacting with a cogenerator, an electric chiller and a natural gas boiler, have been investigated in TRNSYS™ environment. The analysis showed that a MILGO based Air Handling Unit has better energy, environmental and economic performances than a conventional, silica gel based one with, in the best case scenario, a fuel energy saving ratio and equivalent CO2 avoided emission of 20.5%, and operating cost saving of 369 €·y −1 .